Preparation method of high-barrier antibacterial natural cellulose-based packaging material

Through the stacking of high-purity α-cellulose and chemical mechanical slurry and the treatment of 1-butyl-3-methylimidazole salt solution, combined with chitosan composite metal nanoparticles, the barrier of natural cellulose-based materials was solved. , the problem of insufficient flexibility and antibacterial properties has achieved efficient and economical preparation of high-performance packaging materials.

CN119121696AActive Publication Date: 2024-12-13GUANGDONG GUANHAO NEW MATERIALS R&D CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411403756.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-13
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The application of existing natural cellulose-based materials in the field of high-quality packaging is limited by their poor barrier properties, flexibility and antibacterial properties, and their processing costs are high, their complexity is high, and their antibacterial components are poorly stable and their effective time is short.

Method used

采用高纯度α-纤维素与化学机械浆的叠层抄造成型方法,结合1-丁基-3-甲基咪唑盐溶液的功能基转化处理,形成三维网络结构,并通过壳聚糖复合金属 Nanoparticle coating, calendering is performed to improve the barrier, mechanical and antibacterial properties of the material.

Benefits of technology

It has achieved efficient and economical improvement of barrier, mechanical and antibacterial properties of natural cellulose-based materials, forming high-performance packaging materials suitable for a variety of packaging scenarios, with good transparency adjustment and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121696A_ABST
    Figure CN119121696A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-barrier antibacterial natural cellulose-based packaging material, which comprises the following steps: taking alpha-cellulose dissolving pulp, pulping to prepare pulp, taking chemimechanical pulp containing cellulose, lignin and hemicellulose, mixing and pulping with the alpha-cellulose pulp to prepare mixed pulp, and drying to obtain the high-barrier antibacterial natural cellulose-based packaging material. The preparation method comprises the following steps: respectively preparing high-purity alpha-cellulose pulp and mixed pulp into pulp making pools, carrying out net stacking and papermaking to form composite paper with alpha-cellulose layers on the surface and the bottom layer and a mixed cellulose layer on the core layer, soaking the composite paper in a functional group conversion solution, washing, soaking in a solution such as ethanol, and drying to obtain the composite paper with the alpha-cellulose layers on the surface and the bottom layer. Preparing chitosan into a chitosan compound solution, coating the surface of the cellulose wet film with the chitosan compound solution, and carrying out calendering treatment to form the packaging material; a multi-layer structure is formed through papermaking, the tensile strength of the material is improved through ionic solution impregnation, the oxygen barrier performance is improved through dehydration impregnation, the surface of a film body material is coated with chitosan composite metal nanoparticles, the antibacterial performance is improved, and the packaging material with excellent comprehensive performance is integrally formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of packaging material preparation or papermaking, and in particular to a method for preparing a high-barrier antibacterial natural cellulose-based packaging material. Background Art

[0002] Natural cellulose-based materials such as wood pulp, bamboo pulp, cotton and linen pulp and dissolving pulp have good biodegradability and environmental friendliness, and are widely used in packaging and other fields. With the increasing shortage of petroleum resources and people's increasing awareness of environmental protection, natural cellulose-based materials, as renewable polymer compounds abundant in nature, have received special attention. How to efficiently develop and utilize the renewable resources of natural cellulose-based materials has become an important direction of the sustainable development strategy.

[0003] For a type of natural cellulose-based materials used in high-quality packaging, they are required to have good barrier properties, and have high barrier properties to water vapor, oxygen, oil, and volatile organic compounds. High barrier properties are essential for maintaining the quality of products in the package, extending shelf life, and reducing food waste. At present, general natural cellulose-based materials have poor barrier properties, which can easily lead to deterioration or performance degradation of the packaged products, limiting their application in high-demand packaging fields, such as food, medicine, and chemical packaging; packaging materials are also required to have good flexibility (poor mechanical properties) and a certain optical transparency (optical ability), while the texture of general regenerated cellulose films is relatively soft (poor mechanical properties), while paper is relatively hard, which is inconvenient to be used in some protective packaging fields. Plastic films have poor recyclability and are difficult to adjust transparency (poor optical properties); in addition, if packaging materials are used in areas that directly contact food, some medical supplies, and biological supplies, they are also required to have certain antibacterial properties.

[0004] In the prior art, the barrier properties of natural cellulose-based materials are generally improved mainly by adding inorganic nanoparticles, nanofiber materials, coating or laminating synthetic polymers, or adopting multi-layer co-extrusion and other methods, and at the same time, components such as maleic anhydride are added to improve the mechanical properties of the materials; however, such methods usually have high production and processing costs, large processing complexity, and the presence of some harmful substances in the processing process causes harm to the environment and human health.

[0005] In order to meet the requirements of antibacterial performance, the antibacterial effect is generally achieved by adding components such as antioxidants, imidazoles, thiazoles and yeast extracts during the processing of packaging materials or after molding; however, simply adding antibacterial components has problems such as weak antibacterial effect, poor stability of antibacterial components, short effective time, and easy separation and shedding of antibacterial components.

[0006] Therefore, in view of the above background and problems, it is necessary to provide a method for preparing a natural cellulose-based packaging material with high barrier and antibacterial properties. Summary of the invention

[0007] The present invention aims to provide a method for preparing a natural cellulose-based packaging material with high barrier and antibacterial properties, in view of the high processing cost and difficulty of the existing technology for preparing natural cellulose-based materials, as well as the poor barrier properties and weak antibacterial properties of the materials. The preparation method comprises the following steps: S10: taking α-cellulose dissolving pulp with a purity of 95% to 100%, pre-impregnating it in a softener, and then beating it to form a high-purity α-cellulose pulp; taking a chemical mechanical pulp containing cellulose, lignin and hemicellulose, mixing the high-purity α-cellulose pulp with the chemical mechanical pulp, and beating them to form a mixed cellulose pulp; S20: using the high-purity α-cellulose pulp and the mixed cellulose pulp to form a papermaking pool, respectively, adding a wet strength agent to each of them and mixing them evenly, and adopting a stacked mesh papermaking method to prepare a cellulose composite paper; the cellulose composite paper is composed of a surface layer, a core layer and a bottom layer stacked in sequence, the surface layer and the bottom layer are material layers of the high-purity α-cellulose pulp, and the core layer is a material layer of the mixed cellulose pulp; S30: heating the functional group conversion solution, placing the cellulose composite paper into the functional group conversion solution for a first immersion, and then washing with distilled water to form functional group converted cellulose; S40: placing the functional group-converted cellulose substrate into a single-component solution of ethanol, isopropanol or n-butanol or a two-component mixed solution or a two-component mixed solution for a second immersion to form a cellulose wet film; S50: taking chitosan, glycerol and acetic acid solution, dissolving chitosan and glycerol in acetic acid solution to form a chitosan composite solution, and applying the chitosan composite solution to the surface of the cellulose wet film to form a high barrier antibacterial composite film; S60: performing calendering treatment on the high barrier antibacterial composite film to form the high barrier antibacterial natural cellulose-based packaging material.

[0008] Furthermore, forming the high-barrier antibacterial composite film also includes: taking nano-titanium dioxide or nano-silver or nano-zinc oxide, and evenly dispersing it into the chitosan composite sugar solution to form a chitosan composite metal nanoparticle solution; coating the chitosan composite metal nanoparticle solution onto the surface of the cellulose wet film to form the high-barrier antibacterial composite film.

[0009] Furthermore, the softener is silicone oil or sodium stearate.

[0010] Furthermore, the beating degree of the dissolving pulp is 40°SR to 70°SR; and the beating degree of the chemical mechanical pulp is 18°SR to 38°SR.

[0011] Furthermore, the addition amount of the wet strength agent is 20kg / ton to 80kg / ton.

[0012] Furthermore, the functional group conversion solution is a 1-butyl-3-methylimidazolium salt solution, and the 1-butyl-3-methylimidazolium salt is one of 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM]PF6), 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM]BF4), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([BMIM]NTf2), 1-butyl-3-methylimidazolium trifluoromethyl acetate ([BMIM]CF3COO), 1-butyl-3-methylimidazolium nitrate ([BMIM]NO3) or 1-butyl-3-methylimidazolium nitrite ([BMIM]NO2).

[0013] Furthermore, the functional group conversion solution also contains nano silica sol.

[0014] Furthermore, the volume concentration of the single-component solution or the two-component mixed solution or the two or more-component mixed solution is 98% to 100%.

[0015] Furthermore, the pre-impregnation time is 30 minutes to 60 minutes; the first impregnation time is 30 minutes to 90 minutes; and the second impregnation time is 4 hours to 12 hours.

[0016] Furthermore, the calendering treatment is carried out using a calendering machine, and the conditions of the calendering treatment are: temperature of 100° C. to 220° C., line pressure of 20 kN / m to 100 kN / m, and vehicle speed of 30 m / min to 300 m / min.

[0017] The technical solution of the present invention adopts α-cellulose with a high beating degree to form a surface layer and a bottom layer, and adopts α-cellulose with a high beating degree and chemical mechanical pulp with a low beating degree to form a core layer, so that the material has strong tensile strength (mechanical properties) and stiffness in terms of physical properties, and uses 1-butyl-3-methylimidazole salt solution to impregnate the formed cellulose composite paper under certain temperature conditions, selectively dissolves α-cellulose, but does not dissolve lignin and hemicellulose, effectively improves the tensile strength and stiffness of the material, and regulates the opacity and oxygen barrier properties of the material, and then uses a solution formed by components such as ethanol, isopropanol and n-butanol to impregnate and replace the material, removes water and solvents in the aforementioned materials, so that the material forms a three-dimensional network structure and increases the oxygen barrier properties; and prepares a chitosan composite metal nanoparticle solution, which is coated on the membrane material to form an anti-resistance component adsorbed on the chitosan through hydrogen bonding, thereby It is adsorbed on the surface of the material and is not easy to fall off, forming a film material with strong antibacterial properties and long antibacterial effect. At the same time, chitosan and metal nanoparticles further improve the flexibility (mechanical properties) of the material; the formed packaging material has enhanced mechanical properties relative to regenerated cellulose film, is softer in texture than paper materials, and is recyclable and has adjustable transparency (good optical properties) relative to plastic films; the material is hot-pressed by calendering treatment to effectively remove volatile solvents in the material, so that the three-dimensional network structure forms an irreversible structure, and improves the bonding strength between material layers, thereby improving the stability of the material; the overall production method forms an overall process with effective coordination before and after, which has the beneficial effects of simple material use, low processing cost and simple processing process, and improves the operability of preparing efficient, economical and environmentally friendly high-barrier and antibacterial natural cellulose-based packaging materials with high barrier properties, mechanical properties and antibacterial properties, and the formed packaging materials can meet the needs of many packaging scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0019] Figure 1 is a process flow chart of a preparation method according to an embodiment of the present invention; Figure 2 The actual picture and surface SEM picture of the cellulose composite paper formed by papermaking; Figure 3 A schematic diagram of the cross-sectional structure of cellulose composite paper formed by papermaking; Figure 4 The diagram is the mechanism of dissolving cellulose by the functional group conversion solution system; Figure 5 This is a diagram of the mechanism of action of cellulose and 1-butyl-3-methylimidazolium salt solution; Figure 6 Schematic diagram of nano-silica sol loaded with cellulose; Figure 7 Schematic diagram of the three-dimensional macromolecular network structure of cellulose wet film; Figure 8 This is the SEM image of nano-titanium dioxide particles uniformly dispersed on the surface of cellulose wet film; Fig. 9 1 and 2 are Fourier transform infrared spectra (FTIR) of the regenerated cellulose material (RC) and the material of this embodiment (CMF).

[0020] Description of Figure Numbers: Surface layer: 110; core layer: 120; bottom layer: 130.

[0021] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, inside, outside...) are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0024] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0025] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0026] See also Figure 1 , Figure 1 The present invention is a process flow chart of the preparation method according to the embodiment of the present invention.

[0027] The method for preparing the high barrier performance and high barrier antibacterial natural cellulose-based packaging material provided by the embodiment of the present invention comprises: Figure 1 The steps in the process flow chart are described in detail as follows.

[0028] Step S10: Take α-cellulose dissolving pulp with a purity of 95% to 100%, place it in a softener of silicone oil or sodium stearate for pre-impregnation (the bath ratio of α-cellulose: softener is 5:1 to 20:1, the amount of softener is 10 g / L, and the pre-impregnation time is 30 minutes to 60 minutes), then beat it to form a pulp with a beating degree of 40°SR to 70°, and prepare high-purity α-cellulose pulp.

[0029] Take a chemical mechanical pulp containing cellulose, lignin and hemicellulose and having a beating degree of 18°SR to 38°SR, mix and beat the high-purity α-cellulose pulp with the chemical mechanical pulp in a mass ratio of 1:5 to 5:1, and then prepare a mixed cellulose pulp, which can also be further made into a mixed cellulose pulp board for subsequent use.

[0030] In this embodiment, high-purity α-cellulose is selected, which has a uniform molecular weight distribution to ensure the mechanical strength and transparency of the substrate.

[0031] Pre-impregnation with a softener before pulping can reduce the fiber breakage rate, thereby reducing the friction coefficient of the bottom layer 130 and the surface layer 110 of the subsequent papermaking to form the cellulose composite paper, improving the smoothness, making the subsequent processing to form the packaging material production process smoother, and reducing problems such as accumulation and blockage caused by the large friction coefficient of the material, thereby reducing equipment failures and production interruptions, and improving overall production efficiency.

[0032] In this embodiment, the α-cellulose dissolving pulp is treated with a high beating temperature of 40°SR to 70°SR. On the one hand, it can improve the degree of fiber softening, fibrillation and kink curling, which helps to improve the flexibility of the subsequent packaging material. On the other hand, it can improve the swelling properties of the dissolving pulp when immersed in the subsequent functional base conversion solution, which is beneficial to the subsequent cellulose dissolution and substrate performance regulation. The α-cellulose dissolving pulp forms a surface layer 110 and a bottom layer 130 during papermaking.

[0033] In this embodiment, the chemical mechanical pulp contains three major components, namely cellulose, lignin and hemicellulose, and the three major components have significant differences in chemical structure and physical properties. During the subsequent first impregnation, the functional group conversion solution can selectively dissolve cellulose but not lignin and hemicellulose, so that the cellulose composite paper to be formed can maintain strength and stiffness during the subsequent first impregnation process and is not easy to break; the high-purity α-cellulose pulp and the chemical mechanical pulp are mixed in different mass ratios of 1:5 to 5:1, while ensuring the stiffness of the material, the opacity and oxygen barrier properties of the material are formed into a state that can be regulated by the mass ratio; the low beating degree of 18°SR to 38°SR is used to reduce the cutting of fibers, maintain a longer fiber length, further enhance the stiffness, and make the material processable for coating and printing; the mixed cellulose pulp forms a core layer 120 during the subsequent papermaking.

[0034] See also Figure 2 , Figure 2 This is the actual picture and surface SEM picture of the cellulose composite paper formed by papermaking.

[0035] It can be seen that through the preparation method of this embodiment, a good film is prepared and formed; Figure 2 Comparing the actual pictures of F0 and F1 films, we can see that F0 film has higher transparency than F1 film, which means that the film has the effect of adjustable transparency (good optical performance). Figure 2 Comparing the SEM images of F0 and F1, it can be seen that the density of the films is relatively high, indicating that the films have good barrier properties and oxygen barrier properties; this is because the opacity and oxygen barrier properties of the substrate can be controlled by adjusting the different mass ratios of α-cellulose, lignin, hemicellulose and cellulose in the core layer 120.

[0036] See also Figure 3 , Figure 3 Schematic diagram of the cross-sectional structure of cellulose composite paper.

[0037] Step S20: High-purity α-cellulose pulp and the mixed cellulose pulp are used to prepare papermaking pulp pools, and 20kg / ton to 80kg / ton of pulp wet strength agent (the wet strength agent can make the cellulose composite paper have a certain wet strength) is added respectively, mixed evenly, and a one-time stacking screen papermaking molding method is adopted to prepare cellulose composite paper.

[0038] The cellulose composite paper is composed of a surface layer, a core layer and a bottom layer which are partially infiltrated and laminated in sequence. The surface layer and the bottom layer are material layers of the high-purity α-cellulose pulp, and the core layer is a material layer of the mixed cellulose pulp.

[0039] The three-layer composite paper structure formed in this embodiment provides the basic conditions for providing different properties of each layer of materials in the subsequent functional base conversion solution, so that the impregnation can dissolve the cellulose in the surface layer, bottom layer and core layer but not dissolve the lignin and hemicellulose in the core layer.

[0040] See also Figure 4 and Figure 5 , Figure 4 The diagram is the mechanism diagram of cellulose dissolution by functional group conversion solution system. Figure 5 This is a diagram showing the mechanism of action of cellulose with 1-butyl-3-methylimidazolium salt solution.

[0041] Step S30: A functional group conversion solution of 1-butyl-3-methylimidazolium salt solution is prepared, wherein the concentration of the functional group conversion solution is 1 mL / g to 10 mL / g compared to the mixed cellulose pulp, and the solution is heated to 30° C. to 150° C. by microwave heating. The cellulose composite paper is placed in the functional group conversion solution for the first immersion, and then washed with distilled water after immersion for 30 to 90 minutes to form functional group converted cellulose.

[0042] In this embodiment, the main active ingredient of the functional group conversion solution is: 1-butyl-3-methylimidazolium salt solution, which has green and environmentally friendly properties, has good solubility in cellulose, and has low solubility in lignin and hemicellulose.

[0043] By utilizing the differences in chemical structures and physical properties of cellulose, lignin and hemicellulose, when the cellulose composite paper is immersed in a functional base conversion solution, the cellulose is effectively dissolved while the lignin and hemicellulose are almost insoluble.

[0044] Cellulose is a highly crystalline polymer, mainly composed of β-(1→4) linked D-glucose units, with a large number of hydrogen bonds within and between molecules, and 1-butyl-3-methylimidazolium salt can cause the surface of α-cellulose and cellulose to swell, and the salt molecules penetrate into the α-cellulose and cellulose chains, destroying the regular structure of the surface to form amorphous cellulose, and the functional group conversion solution of 1-butyl-3-methylimidazolium salt solution can break the hydrogen bonds to dissolve cellulose; the main component of the surface layer is α-cellulose, and the core layer mixed cellulose contains cellulose, and the hydroxyl groups of α-cellulose and cellulose interact with the cations of the functional group conversion solution, while the hydroxyl hydrogens interact with the anions, weakening the hydrogen bonds within and between molecules, resulting in the cracking of the molecular chains, so that α-cellulose and cellulose are dissolved in the ionic liquid.

[0045] Lignin is a complex phenolic polymer with a complex aromatic structure and a large number of methylated and phenoxylated side chains, while hemicellulose is a mixture of a series of different glycoside units; the interaction between the functional group conversion solution of 1-butyl-3-methylimidazolium salt solution and cellulose is stronger than the interaction with lignin or hemicellulose, thereby preferentially dissolving cellulose; in addition, the interaction between lignin and hemicellulose also hinders the dissolution of both in ionic liquids.

[0046] The mixed cellulose material layer of the core layer 120 includes lignin and hemicellulose components. The lignin and hemicellulose are covalently bonded and wrapped around the cellulose of the surface layer 110 and the bottom layer 130, making them difficult to dissolve. This allows the core layer 120 to maintain strength and stiffness during subsequent processing such as impregnation, coating and printing. That is, the first impregnation process is not a process in which the glucose or polysaccharide components of the cellulose are dissolved by a solution, but a process in which the cellulose at the molecular microscopic level is opened from long chains to form short chains, and a process in which the fibers at the macroscopic level are fibrillated as a whole. After the first impregnation, the diameter of the cellulose becomes thinner, the material becomes denser, and the transparency and barrier properties are improved. Therefore, the opacity and oxygen barrier properties of the substrate can also be controlled by adjusting the different mass ratios of the α-cellulose of the core layer 120 to lignin, hemicellulose and cellulose.

[0047] Selective dissolution of cellulose can, on the one hand, allow the substrate to maintain strength and stiffness during the impregnation process, and on the other hand, can adjust the opacity and oxygen barrier properties of the substrate.

[0048] 1-Butyl-3-methylimidazolium salt solution (BMIM) is a cationic component that can be combined with other anions to form a variety of ionic liquids; specifically, it includes 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM]PF6), 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM]BF4), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([BMIM]NTf2), 1-butyl-3-methylimidazolium trifluoromethyl acetate ([BMIM]CF3COO), 1-butyl-3-methylimidazolium nitrate ([BMIM]NO3) or 1-butyl-3-methylimidazolium nitrite ([BMIM]NO2), etc.

[0049] The first impregnation adopts microwave heating. The lower temperature treatment can effectively reduce the dissolution and cutting effect on the fiber, so that the fiber has the characteristics of longer average length, higher substrate strength and higher opacity. When the impregnation temperature is above 150°C, the ionic liquid has a severe destructive effect on the fiber structure, resulting in a significant reduction in fiber length, low substrate opacity and poor oxygen barrier effect. The first impregnation time is 30 minutes to 90 minutes. The longer the impregnation time is, the higher the degree of fiber swelling, the lower the substrate opacity and the better the oxygen barrier performance.

[0050] See also Figure 6 , Figure 6 Schematic diagram of nano-silica sol loaded with cellulose.

[0051] In one embodiment, the functional group conversion solution further comprises nano silica sol, and the amount thereof is 0.5% to 3.0% by weight relative to the mass ratio of the functional group converted cellulose.

[0052] Nano-silica sol particles with a high specific surface area are compounded with 1-butyl-3-methylimidazole salt solutions. During the first impregnation, the nano-silica sol can be evenly distributed in the fiber microscopic surface layer of the cellulose composite paper, reducing the friction between the direct contact surfaces, thereby reducing the friction coefficient and providing a smoother material basis for subsequent film processing.

[0053] See also Figure 7 , Figure 7 Schematic diagram of the three-dimensional macromolecular network structure of cellulose wet membrane.

[0054] Step S40: The functional group-converted cellulose formed in step S30 is placed in a single-component solution of ethanol, isopropanol or n-butanol or a mixed-component solution of two or more components for a second immersion, and the volume concentration of the solution is 98% to 100%. Preferably, a mixed solution formed by mixing three components with volume concentrations of 20% to 30% ethanol, 20% to 30% isopropanol, and 20% to 30% n-butanol is used for the second immersion, and the immersion time is 4 hours to 12 hours to form a cellulose wet film.

[0055] In this embodiment, a solution such as ethanol, isopropanol or n-butanol is used as a displacement solution, and the functional group-converted cellulose is placed in the displacement solution to displace and remove the residual water and solvent in the functional group-converted cellulose, thereby finally forming a cellulose wet film with a three-dimensional macromolecular network structure.

[0056] It is worth noting that after the second impregnation, the ethanol, isopropanol or n-butanol in the mixed component solution can be recovered and reused by distillation or the like.

[0057] Different replacement solutions have different volatilities and solubility in the substrate, which affects the replacement efficiency; the volatility of ethanol, isopropanol and n-butanol decreases in turn, and longer time is required for complete replacement. The solvent replacement time is 4 to 12 hours.

[0058] The polarity of the organic solvents in the above-mentioned different replacement solutions is different from that of water, and they can effectively interact with the water molecules in the functional group-converted cellulose, and gradually replace the water molecules through the dissolution and diffusion process; as the water molecules are replaced by the organic solvent, the three-dimensional network structure in the substrate gradually stabilizes; before the water is completely replaced, the structure of the substrate will undergo a certain deformation or contraction, and after the replacement is completed, the organic solvent fills the space originally occupied by the water molecules and regains the integrity of the network structure; the use of organic solvents with different polarities affects the non-directionality and structural complexity of the network structure formed during the molecular replacement process. This non-directional, complex-structured three-dimensional macromolecular network structure can, on the one hand, increase the path length of oxygen molecules penetrating the paper and enhance the oxygen barrier performance; on the other hand, it can enhance the strength of the material itself, ensure that the material is not easy to break during coating and printing, effectively improve the subsequent processability, and meet packaging applications.

[0059] Step S50: Take chitosan with a deacetylation degree of 80% to 95%, glycerol and a volume fraction of 1% acetic acid solution, and dissolve chitosan and glycerol in the acetic acid solution in a mass ratio of 2:0.4:100 to 3.5:0.7:100, preferably 3:0.6:100, to form a chitosan composite solution, which is applied to the surface of the cellulose wet film to form a high barrier antibacterial composite film.

[0060] Chitosan has excellent properties such as antibacterial, biocompatibility and non-toxicity, but the composite membrane prepared by directly blending it with cellulose is prone to phase separation and difficult co-solubility, resulting in a low chitosan content on the surface of the cellulose wet film and weakened antibacterial properties. Therefore, by blending chitosan with glycerol and acetic acid solution to form a composite system, the polarity and acidity of glycerol and acetic acid solution on the cellulose wet film are utilized to cause a graft copolymerization reaction between chitosan and the surface of the cellulose wet film, thereby greatly increasing the content of chitosan on the surface of the cellulose wet film.

[0061] See also Figure 8 , Figure 8 This is a SEM image of nano-titanium dioxide particles evenly dispersed on the surface of cellulose wet film.

[0062] In one embodiment, the process of forming a high-barrier antibacterial composite film also includes: taking nano-titanium dioxide or nano-silver or nano-zinc oxide, and evenly dispersing it into the chitosan compound solution to form a chitosan composite metal nanoparticle solution; wherein the mass fraction of the metal nanoparticles is: 0.1% to 0.3%; coating the chitosan composite metal nanoparticle solution onto the surface of the cellulose wet film to form the high-barrier antibacterial composite film.

[0063] Metal nanoparticles such as nanosilver, nanotitanium dioxide and nanozinc oxide have strong antibacterial properties (generally capable of killing bacteria such as Escherichia coli) and good heat resistance; preferably, nanotitanium dioxide (TiO2) has inert, non-toxic and photocatalytic antibacterial properties; metal nanoparticles can be adsorbed on chitosan through intermolecular hydrogen bonds, thereby forming a more solid and effective bond with the film body, and are not easy to fall off during use, thereby effectively improving the antibacterial ability and antibacterial time.

[0064] It is worth noting that chitosan and metal nanoparticles not only have good antibacterial effects, but also can improve the tensile strength (mechanical ability) of the high barrier antibacterial composite film. Since chitosan and metal nanoparticles are adsorbed on the surface of the cellulose wet film through hydrogen bonding, the metal nanoparticles are evenly dispersed on the surface of the chitosan, which effectively improves the strength of the film. In addition, the amount of metal nanoparticles used can further adjust the optical transparency (optical ability) of the high barrier antibacterial composite film. Figure 8 It can be seen that the titanium dioxide particles in the dark area of ​​the figure (white dots in the figure) are evenly distributed on the surface of the high barrier antibacterial composite film and embedded in the chitosan matrix.

[0065] Step S60: The high barrier antibacterial composite film formed in step S50 is calendered using a calender. The cellulose wet film is calendered at a temperature of 100° C. to 220° C., a line pressure of 20 kN / m to 100 kN / m, and a vehicle speed of 30 m / min to 300 m / min to form the high barrier antibacterial natural cellulose-based packaging material.

[0066] After the replacement is completed using the replacement solution, the organic solvent will remain in the cellulose wet film; however, in the present embodiment, ethanol, isopropanol or n-butanol are all highly volatile solvents, which are easy to completely remove (compared with low-volatility solvents that are not easy to remove, which has an adverse effect on subsequent processing and packaging applications); the calendering treatment using heating combined with pressurization has a high curing efficiency, which can efficiently and thoroughly remove the organic solvent to ensure that there is no residue, and can rapidly solidify the macromolecular network in the cellulose wet film to form an irreversible three-dimensional network structure. Hot pressing improves the interlayer bonding strength of the high-barrier and antibacterial natural cellulose-based packaging material, which has higher stability during transportation and storage. After being made into a packaging bag, it can protect the contents from damage.

[0067] The high-barrier antibacterial natural cellulose-based packaging material produced by the above implementation method was compared with the regenerated cellulose film, white kraft packaging paper and PE / PET film in the prior art through performance testing, as shown in Table 1 below.

[0068] Table 1 Performance test comparison data table

[0069] It can be seen that the high-barrier and antibacterial natural cellulose-based packaging materials are superior to the existing film materials in terms of barrier properties (oxygen permeability), mechanical properties (longitudinal tensile strength and transverse tensile strength), stiffness (longitudinal bending stiffness and transverse bending stiffness), flexibility (folding endurance), optical transparency (opacity) and antibacterial properties.

[0070] See also Fig. 9 , Fig. 9 1 and 2 are Fourier transform infrared spectra (FTIR) of the regenerated cellulose material (RC) and the material of this embodiment (CMF).

[0071] The material of this embodiment (high barrier antibacterial high barrier antibacterial natural cellulose-based packaging material, CMF in the figure) uses chitosan and titanium dioxide as added components. The FTIR spectrum shows NH bond stretching vibration peaks at 1564cm and 1558cm, which are characteristic absorption peaks of chitosan amide II group, indicating that chitosan is successfully coated on the surface of cellulose wet film. In addition, the FTIR spectrum of CMF shows that the peak at 600cm -1 Up to 700cm -1 The presence of the stretching vibration peak of Ti-O indicates that the titanium dioxide particles are adsorbed on chitosan through intermolecular hydrogen bonding.

[0072] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a high barrier and antibacterial natural cellulose-based packaging material, characterized in that: The preparation method comprises the following steps: S10: taking α-cellulose dissolving pulp with a purity of 95% to 100%, pre-impregnating it in a softener, and then beating it to form a high-purity α-cellulose pulp; Taking chemical mechanical pulp containing cellulose, lignin and hemicellulose, mixing and beating the high-purity α-cellulose pulp with the chemical mechanical pulp to form a mixed cellulose pulp; S20: using the high-purity α-cellulose pulp and the mixed cellulose pulp to form papermaking pulp pools, respectively, adding wet strength agents to the pulp pools and mixing them evenly, and adopting a stacked mesh papermaking method to prepare cellulose composite paper; The cellulose composite paper is composed of a surface layer, a core layer and a bottom layer which are partially interpenetrated and laminated in sequence, the surface layer and the bottom layer are material layers of the high-purity α-cellulose pulp, and the core layer is a material layer of the mixed cellulose pulp; S30: heating the functional group conversion solution, placing the cellulose composite paper into the functional group conversion solution for a first immersion, and then washing with distilled water to form functional group converted cellulose; S40: placing the functional group-converted cellulose substrate into a single-component solution of ethanol, isopropanol or n-butanol or a two-component mixed solution or a two-component mixed solution for a second immersion to form a cellulose wet film; S50: taking chitosan, glycerol and acetic acid solution, dissolving chitosan and glycerol in the acetic acid solution to form a chitosan composite solution, and applying the chitosan composite solution to the surface of the cellulose wet film to form a high barrier antibacterial composite film; S60: performing calendering treatment on the high barrier antibacterial composite film to form the high barrier antibacterial natural cellulose-based packaging material.

2. The method for preparing a high barrier and antibacterial natural cellulose-based packaging material according to claim 1, characterized in that: Forming the high barrier antibacterial composite film also includes: Taking nano titanium dioxide or nano silver or nano zinc oxide, and evenly dispersing it into the chitosan composite sugar solution to form a chitosan composite metal nanoparticle solution; The chitosan composite metal nanoparticle solution is coated on the surface of the cellulose wet film to form the high barrier antibacterial composite film.

3. The method for preparing a high barrier and antibacterial natural cellulose-based packaging material according to claim 1 or 2, characterized in that: The softener is silicone oil or sodium stearate.

4. The method for preparing a high barrier and antibacterial natural cellulose-based packaging material according to claim 1 or 2, characterized in that: The beating degree of the dissolving pulp is 40°SR to 70°SR; the beating degree of the chemical mechanical pulp is 18°SR to 38°SR.

5. The method for preparing a high barrier and antibacterial natural cellulose-based packaging material according to claim 1 or 2, characterized in that: The addition amount of the wet strength agent is 20kg / ton to 80kg / ton.

6. The method for preparing a high barrier and antibacterial natural cellulose-based packaging material according to claim 1 or 2, characterized in that: The functional group conversion solution is a 1-butyl-3-methylimidazolium salt solution, and the 1-butyl-3-methylimidazolium salt is one of 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM]PF6), 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM]BF4), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([BMIM]NTf2), 1-butyl-3-methylimidazolium trifluoromethyl acetate ([BMIM]CF3COO), 1-butyl-3-methylimidazolium nitrate ([BMIM]NO3) or 1-butyl-3-methylimidazolium nitrite ([BMIM]NO2).

7. The method for preparing a high barrier and antibacterial natural cellulose-based packaging material according to claim 6, characterized in that: The functional group conversion solution also contains nano silica sol.

8. The method for preparing a high barrier and antibacterial natural cellulose-based packaging material according to claim 1 or 2, characterized in that: The volume concentration of the single-component solution or the two-component mixed solution or the two or more-component mixed solution is 98% to 100%.

9. The method for preparing a high barrier and antibacterial natural cellulose-based packaging material according to claim 1 or 2, characterized in that: The pre-impregnation time is 30 minutes to 60 minutes; the first impregnation time is 30 minutes to 90 minutes; and the second impregnation time is 4 hours to 12 hours.

10. The method for preparing a high barrier and antibacterial natural cellulose-based packaging material according to claim 1 or 2, characterized in that: The calendering treatment is performed using a calendering machine, and the conditions of the calendering treatment are: temperature of 100° C. to 220° C., line pressure of 20 kN / m to 100 kN / m, and vehicle speed of 30 m / min to 300 m / min.

Citation Information

Patent Citations

  • Chitosan / titanium dioxide nano-composite antibacterial coating preparation method

    CN105200856A

  • Preparation method of hydrophobic oilproof paper

    CN108625219A

  • Preparation method of high-strength antibacterial coated paper

    CN111663368A

  • Completely biodegradable high-barrier packaging material as well as preparation method and application thereof

    CN117626717A

  • Method for producing paper having wet strength

    JP2016138339A